Bio-equivalence study of two oral doxycycline formulations (doxycycline kela 75%Â® and mebcodox 75%Â®) in broiler Chickens - El-Komy, Ashraf; Aboubakr, Mohamed (International Journal of Pharmacology and Toxicology, 2020)
The present study was designed to assess the comparative bio-equivalence of Doxycycline Kela 75%Â® and Mebcodox 75%Â® in healthy broiler chickens after oral administration of both products in a dose of 20 mg doxycycline base/kg.b.wt. Twenty four broiler chickens were divided into two groups. The first group was designed to study the pharmacokinetics of Doxycycline Kela 75%Â®, while the 2nd group was designed to study the pharmacokinetics of Mebcodox 75%Â®. Each broiler chickens in both groups were orally administered with 20 mg doxycycline base/kg.b.wt. Blood samples were obtained from the wing vein and collected immediately before and at 0.08, 0.16, 0.25, 0.5, 1, 2, 4, 6, 8, 12 and 24 hours after a single oral administration The disposition kinetics of Doxycycline Kela 75%Â® and Mebcodox 75%Â® following oral administration of 20 mg doxycycline base/kg.b.wt. revealed that the maximum blood concentration [Cmax] were 3.35 and 3.28 Î¼g/ml and attained at [tmax] of 0.97 and 0.99 hours, respectively.In conclusion: Mebcodox 75%Â® is bioequivalent to Doxycycline Kela 75%Â® since the ratios of Cmax, AUC0-24 and AUC0-âˆž (T/R) was 0.97, 0.95 and 0.94 respectively. These are within the bioequivalence acceptance range. Mebcodox 75%Â® and Doxycycline Kela 75%Â® are therefore bioequivalent and interchangeable.Â Â Â